(untitled) (International Journal of Mathematics and Physics, 2015)
The solution of the inverse problem is to restore the nonlinearity arameters based on some additional information. A new method is resented as an example of a nonlinear inverse problem for a model of the dynamics of the gas mixture based on the models of cloud formation. The unknowns are the parameters of the nonlinearity in the right-hand sides of equations of hydrodynamics. The solving of the inverse problem is to restore the nonlinearity parameters based on some additional formation. Our method is presented as an example of a nonlinear inverse problem for a model of the dynamics of the gas mixture based on the models of cloud formation. The unknowns are the parameters of the nonlinearity in the right-hand sides of equations of hydrodynamics. On the basis of numerical experiments of solving of the direct problem identified flow characteristics that are sensitive to changes in the searching parameters. Then the data bank is formed on the grid of these parameters, which allows to find the best approximation of given set of characteristics.